Cicero Varsoviensis, XXX annis post - Cicero in Warsaw 30 Years Later - Ermanno Malaspina; Jerzy Axer (Ciceroniana On Line)
The idea of education in the spirit of artes liberales is one of the proposals for building a community of humanists bound together by the respect for diversity and love of freedom. Cicero can be a teacher for such a community, and his legacy and his fate can be a significant reminder.